The Effect Of Problem-Based Learning Model Based On Quizizz Media On Ict Learning Outcomes Of Grade V Students - Ardhy, Muhammad Khazainul Ardhy Tenrilengka; Musbaing, Musbaing; Rahmawati, Rahmawati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
In preliminary observations on March 5, 2024 at SDIT Ar-Rahmah Makassar city, there are still many students who have difficulty understanding the material taught in the learning process marked by the low learning outcomes of ICT students. This study aims to analyze the effect of Problem Based Learning learning model based on Quizizz media on ICT learning outcomes of fifth grade students of SDIT Ar-Rahmah Makassar City. The type of research used is the experimental method. The results showed that the Pretest and Posttest data were normally distributed with a Kolmogorov-Smirnov significance value of 0.167 and Shapiro-Wilk of 0.359. In addition, the homogeneity test results showed that the data had a homogeneous variance with a Levene Statistics significance value of 0.017. Based on the t-test results, there is a difference between the Pretest and Posttest scores, which shows that the Problem Based Learning learning model based on Quizizz media has an effect on student ICT learning outcomes. The average Pretest score of 7.38 increased to 10.31 on the Posttest. These results indicate an increase in student understanding after the application of this learning model. It can be concluded that this model is effective in improving learning outcomes and can encourage students to be more active in the learning process, increase their involvement in understanding the material and provide a more interesting and interactive learning experience.